Bilirubin, platelet activation and heart disease: A missing link to cardiovascular protection in Gilbert's syndrome?. Issue 1 (March 2015) - Kundur, Avinash R.; Singh, Indu; Bulmer, Andrew C.
Abstract: Gilbert's syndrome (GS) is a relatively common condition, inducing a benign, non-hemolytic, unconjugated hyperbilirubinemia. Gilbert's Syndrome is associated with mutation in the Uridine Glucuronosyl Transferase 1A1 (UGT1A1) gene promoter, reducing UGT1A1 activity, which normally conjugates bilirubin allowing its elimination from the blood. Individuals with GS demonstrate mildly elevated plasma antioxidant capacity caused by elevated levels of unconjugated bilirubin (UCB), reduced thiols and glutathione. Interestingly, the development of, and risk of mortality from, cardiovascular disease is remarkably reduced in GS individuals. An explanation for this protection may be explained by bilirubin's ability to inhibit multiple processes that induce platelet hyper-reactivity and thrombosis, thus far under-appreciated in the literature. Reactive oxygen species are produced continuously via metabolic processes and have the potential to oxidatively modify proteins and lipids within cell membranes, which may encourage the development of thrombosis and CVDs. Oxidative stress induced platelet hyper-reactivity significantly increases the risk of thrombosis, which can potentially lead to tissue infarction. Here, we discuss the possible mechanisms by which increased antioxidant status might influence platelet function and link this to cardiovascular protection in GS. In summary, this is the first article to discuss the possible role of bilirubin as an anti-thrombotic agent, which inhibits platelet activation and potentially, organ infarction, which could contribute to the reduced mortality rate in mildly hyperbilirbinemic individuals. Highlights: Elevated levels of bilirubin are associated with reduced risk of cardiovascular disease especially in Gilbert's syndrome. Platelet hyper-activity due to oxidative stress increases the risk of thrombosis, and therefore myocardial infarction. Bilirubin may inhibit platelet activity by interacting with collagen and ADP receptors, or by improving resistance to oxidative stress. Inhibiting platelet activity may represent one mechanism to explain protection against cardiovascular disease leading to mortality in mildly hyperbilirubinemic individuals.